THE INFLUENCE OF FLEXIBLE WORK SCHEDULES, WORK-LIFE BALANCE, AND MANAGERIAL SUPPORT ON INDIVIDUAL PRODUCTIVITY IN A DIGITAL MARKETING COMPANY - Khotimah, Ayyumi Khusnul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Purpose: This study aims to analyze the influence of flexible work schedules, work-life balance, and managerial support on individual productivity in digital marketing companies. As technology evolves and work patterns become more dynamic, digital marketing firms face growing challenges in maintaining employee performance while also providing adequate flexibility and support. This research adopts a quantitative approach using a survey method distributed to employees across several digital marketing companies. The collected data were analyzed using multiple linear regression to examine the relationships and effects among the variables. The results reveal that flexible work schedules, work-life balance, and managerial support have a positive and significant impact on individual productivity. These findings suggest that companies should pay greater attention to implementing flexible work policies and strengthening managerial roles to enhance overall employee performance. Methodology/approach: This study employs a quantitative research design with a causal associative approach, aiming to determine the effects of flexible work schedules, work-life balance, and managerial support on individual productivity in digital marketing companies. Results/findings: The study involved 120 respondents who are full-time employees from various digital marketing companies in Indonesia. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. Limitations: This research has several limitations that should be considered when interpreting the findings and designing future studies. One key limitation is the narrow scope limited to employees in digital marketing companies, which means the results may not be generalizable to other industries with different work characteristics, such as manufacturing or the public sector. Contribution: This study makes an important contribution both theoretically and practically in the field of human resource management, particularly in the context of digital marketing companies. It enriches the academic literature by integrating three critical variables—flexible work schedules, work-life balance, and managerial support—in explaining factors that influence individual productivity. The findings reinforce existing theories on the relationship between adaptive work environments and employee performance and provide empirical evidence within the underexplored context of the digital marketing industry. Novelty: This study offers a novel contribution by specifically exploring the combined influence of flexible work schedules, work-life balance, and managerial support on individual productivity within the digital marketing industry a sector characterized by high demands for creativity, adaptability, and technological agility.